Stimulating Annuity Markets - Ben J. Heijdra; Jochen O. Mierau; Timo Trimborn (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the short-, medium-, and long-run implications of stimulating annuity markets in a dynamic general-equilibrium overlapping-generations model. We find that beneficial partial-equilibrium effects of stimulating annuity markets are counteracted by negative general-equilibrium repercussions. Balancing the positive partial-equilibrium and negative general-equilibrium forces we show that there exists some intermediate level of annuitization such that long-run welfare is maximized. Studying the transition to the optimal degree of annuitization shows that currently middle-aged individuals stand to gain most from the stimulation of annuity markets.
Keywords: C68; D91; J14; H55; 330; individual welfare; annuity markets; computable general equilibrium; overlapping generations